PIECES For Evaluating Registration Information System in The Kasih Ibu Hospital Surakarta - Yunita Wisda Tumarta Arif; Nurhayati; Ni Putu Larasati Janur Mudiari (Proceeding of International Conference on Science, Health, And Technology, 2019)
Kasih Ibu Hospital has a Hospital Management Information System. Based on the preliminary survey, the implementation of SIMRS in the patient registration unit is still not stable. System evaluation is needed so that deficiencies in the implementation of the system are immediately addressed. The method used to evaluate the registration information system is the PIECES Method. The purpose of the evaluation is to conduct an assessment of the performance of the patient registration information system that is already running with the PIECES method based on aspects of performance, information, economic, control and security, service. This research is a descriptive study with cross sectional approach. The object of this study was the patient registration information system and the subjects observed were outpatient and inpatient registration officers who were related to the registration information system. The research instruments were observation guidelines, interview guidelines, and questionnaires. The results of the evaluation of the patient registration information system by the PIECES method at the Kasih Ibu Hospital based on performance aspects, showed the system was able to produce the desired throughput the system was able to carry out the patient registration process. The information system aspect is able to produce accurate information very well. The economic aspects of resources on the system are very good. The integrity control aspect of access to software or data is very good. The efficiency aspect of business reusability to study systems is very good. The service aspect shows that accuracy, computational accuracy and control are good. The conclusion of this study based on the assessment of respondents is that the patient registration information system at the Surakarta Ibu Hospital is categorized as good and can be accepted by respondents.